The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1021/acs.jpcc.6b05700
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Protein Binding to Individual Hydrogel Nanoparticles with Single-Nanoparticle Surface Plasmon Resonance Imaging Microscopy

Abstract: ABSTRACT:The specific binding and uptake of protein molecules to individual hydrogel nanoparticles is measured with real-11 time single-nanoparticle surface plasmon resonance imaging (SPRI) microscopy. Nanoparticles that adsorb onto chemically 12 modified gold thin films interact with traveling surface plasmon polaritons and create individual point diffraction patterns in the 13 SPRI microscopy differential reflectivity images. The intensity of each point diffraction pattern depends on the integrated 14 refrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 49 publications
(69 reference statements)
1
28
0
Order By: Relevance
“…This single nanosphere is consistent with all previously reported works in that it produces a wave-like pattern with parabolic tails on the image (Fig. 2B) acquired using conventional SPRM (SPRM-SDI) ( 7 , 8 , 13 , 15 , 18 ). Both theoretical ( 23 , 24 ) and experimental ( 18 , 25 , 26 ) investigations have indicated that this wave-like pattern is due to the scattered SPs generated by the nanosphere.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…This single nanosphere is consistent with all previously reported works in that it produces a wave-like pattern with parabolic tails on the image (Fig. 2B) acquired using conventional SPRM (SPRM-SDI) ( 7 , 8 , 13 , 15 , 18 ). Both theoretical ( 23 , 24 ) and experimental ( 18 , 25 , 26 ) investigations have indicated that this wave-like pattern is due to the scattered SPs generated by the nanosphere.…”
Section: Resultssupporting
confidence: 92%
“…When compared with the surface-sensitive microscopy techniques of single-molecule TIRFM, SPRM offers the advantageous capability to monitor individual binding events continuously without the need to account for photo bleaching or blinking of the fluorophores. Therefore, in recent years, SPRM has found numerous applications in the study of biological targets, including cells ( 12 ), bacteria ( 13 ), viruses ( 7 ), DNA molecules ( 14 ), and proteins ( 15 ); the local electrochemical reactions of heterogeneous surfaces ( 16 , 17 ); and the catalytic reactions of nanomaterials ( 18 , 19 ). However, SPRM has obvious disadvantages that prevent the general use of this interesting technique.…”
Section: Introductionmentioning
confidence: 99%
“… 41 , 47 In addition to nanoparticle-counting measurements, changes in the intensity of the average single-nanoparticle SPRI response (⟨Δ% R NP ⟩) have been used to quantitate the bioaffinity uptake of polypeptides and proteins by hydrogel nanoparticles. 42 , 43 …”
mentioning
confidence: 99%
“…A variety of nanoscale particles, such as metallic nanoparticles [129], dielectric nanoparticles [130,131], protein nanoparticles [132,133] and single DNA molecules [134,135] have been observed with this system. In addition, orthogonal and complementary measurement techniques, such as electrochemistry [129,136,137] and local thermal measurement [138], have also be incorporated into the system.…”
Section: Surface Plasmon Resonance Imaging Microscopymentioning
confidence: 98%